The Effect of Reward and Punishment on Student Motivation in Muhadatsah Yaumiyyah at Islamic Boarding School of Ar-Royyan Al-Islami/ Ta’tsîru as-Tsawâb wa al-Iqâbi ‘ala Dawâfi’ at-Thullâb fi Muhâdatsah Yaumiyah fi Ma’hadi ar-Rayyân al-Islâmiy - Maas, Rosdiana; Rambe, Pangadilan; Hidayat, Hakmi; Amiruddin, Muhammad (Al-Manar, 2023)
Abstrac: This research aimed at finding out the influence of reward and punishment toward student muhadatsah yaumiyyah motivation partially and simultaneously at Islamic Boarding School of Ar-Royyan Al-Islami.  It was a quantitative research, and it was associated with the samples that were 75 respondents.  The instrument was in the form of questionnaire with Likert scale, and its validity and reliability were tested.  The data were analyzed by using multiple linear regression.  The research finding showed that (1) there was a significant influence of reward toward student motivation for muhadatsah yaumiyyah based the significance score 0.004 lower than 0.005 and the score of tobserved 2.948 higher than 1.665, (2) there was there was a significant influence of punishment toward student motivation for muhadatsah yaumiyyah based the significance score 0.000 lower than 0.005 and the score of tobserved 34.389 higher than 1.665, and (3) there was a significant influence of reward and punishment toward student motivation for muhadatsah yaumiyyah based the significance score 0.000 lower than 0.005 and the score of Fobserved 600.793 higher than Ftable 3.124.  Based on the determination result, reward and punishment influenced student motivation for muhadatsah yaumiyyah 54%, and the rest 46% was influenced by other variables that were not studied in this research.Keywords: Reward and Punishment, Motivation, Muhadatsah Yaumiyyah